2023
DOI: 10.1186/s43044-023-00342-9
|View full text |Cite|
|
Sign up to set email alerts
|

The predictive value of precipitating factors on clinical outcomes in hospitalized patients with decompensated heart failure: insights from the Egyptian cohort in the European Society of Cardiology Heart Failure long-term registry

Abstract: Background Knowledge of the frequency of precipitating factors for acute heart failure (AHF) is important (either new-onset heart failure [NOHF] or worsening heart failure [WHF]), as this can guide strategies for prevention and treatment. Most data come only from Western Europe and North America; nevertheless, geographic differences do exist. We set out to study the prevalence of precipitating factors of AHF and their connection to patient characteristics and in-hospital and long-term mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“… 53 In the REPORT‐HF registry, patients hospitalized for acute decompensated HF and patients with worsening renal function had the highest mortality rates. 54 In accordance with our findings, in the international cohort study by Lam et al, renal function was not revealed as an independent predictor of mortality. However, age and systolic blood pressure had a significant effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 53 In the REPORT‐HF registry, patients hospitalized for acute decompensated HF and patients with worsening renal function had the highest mortality rates. 54 In accordance with our findings, in the international cohort study by Lam et al, renal function was not revealed as an independent predictor of mortality. However, age and systolic blood pressure had a significant effect.…”
Section: Discussionsupporting
confidence: 92%
“…As for acute HF patients, in the recent publication of Lorlowhakarn et al, age, cardiovascular accidents, and NT‐proBNP level were associated with higher 1‐year mortality after acute HF hospitalization 53 . In the REPORT‐HF registry, patients hospitalized for acute decompensated HF and patients with worsening renal function had the highest mortality rates 54 . In accordance with our findings, in the international cohort study by Lam et al, renal function was not revealed as an independent predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of data from the Egyptian cohort in the European Society of Cardiology (ESC) HF long-term registry (ESC-HF-LT-R) revealed that patients who were hospitalized for acute HFpEF had a 1-year mortality rate of 19.4%. 23 According to the Gulf CARE registry, which enrolled patients hospitalized for acute HFpEF in the Arabian Gulf, 1-year mortality was lower at 8.1%; however, 1-year HF hospitalization rates were high at 27%. 24 Much of the burden related to HFpEF can typically be attributed to a high prevalence of co-morbidities, such as dia- betes, obesity, hypertension, anaemia, chronic kidney disease (CKD), atrial fibrillation (AF) and chronic obstructive pulmonary disease (COPD) (Table 2).…”
Section: Burden and Epidemiology Of Heart Failure With Preserved Ejec...mentioning
confidence: 99%
“…HFpEF is associated with a high rate of morbidity and mortality, and patient survival is typically poor. Analysis of data from the Egyptian cohort in the European Society of Cardiology (ESC) HF long‐term registry (ESC‐HF‐LT‐R) revealed that patients who were hospitalized for acute HFpEF had a 1‐year mortality rate of 19.4% 23 . According to the Gulf CARE registry, which enrolled patients hospitalized for acute HFpEF in the Arabian Gulf, 1‐year mortality was lower at 8.1%; however, 1‐year HF hospitalization rates were high at 27% 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation